Fungsi Metafora Kognitif pada Puisi-Puisi Sofyan Daud - Masayu Gay (Kantor Bahasa Provinsi Maluku Utara, 2018)
This study aims to reveal the function of cognitive metaphors, namely communication and education. The functions of communication are poetic and emotional function, while the functions of education are religious, social and historical function. The study was conducted by using the stylistic approach. This type of research is qualitative with Lakoff and Johnson's cognitive metaphor theory. Firstly, the results show the metaphor function of communication cognition on Sofyan Daud's poetry consists of poetic and emotional functions. Both of these functions are expressed by syntagmatic and paradigmatic patterns. The poetic function uses repetition and alliteration sound and assonance parallelism. The effect of beauty is on metaphors, both Indonesian language and vernacular. The melody and euphony sound occurred because of the combination of the alliteration and assonance as regular rhythms. These sounds reflect the poet's emotion. Secondly, the educational metaphor function is expressed analogically by using personification and allegory as a comparison. The analogy is carried out on a vehicle as a source with a particular animal or object as a target (tenor). The analogy embodies the value of local wisdom and history.